2018
DOI: 10.1007/s10494-018-9960-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Chamber Ignition Mechanism: Simulations of Transient Autoignition in a Mixing Layer Between Reactants and Partially-Burnt Products

Abstract: The structure of autoignition in a mixing layer between fully-burnt or partially-burnt combustion products from a methane-air flame at ϕ = 0.85 and a methane-air mixture of a leaner equivalence ratio has been studied with transient diffusion flamelet calculations. This configuration is relevant to scavenged pre-chamber natural-gas engines, where the turbulent jet ejected from the pre-chamber may be quenched or may be composed of fully-burnt products. The degree of reaction in the jet fluid is described by a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…8 shows that for the prechamber with higher volume, the combustion duration is faster. This fact is related, to a certain extent, to the energy release capacity, since when introducing more mixture into the prechamber, greater turbulence and ignition energy available in the main chamber are obtained [12,13]. In order to observe this pattern in more detail, the ignition advance, COV IMEP and MBF percentage values for each configuration according to the crank angle are presented in Table 4.…”
Section: Combustion Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…8 shows that for the prechamber with higher volume, the combustion duration is faster. This fact is related, to a certain extent, to the energy release capacity, since when introducing more mixture into the prechamber, greater turbulence and ignition energy available in the main chamber are obtained [12,13]. In order to observe this pattern in more detail, the ignition advance, COV IMEP and MBF percentage values for each configuration according to the crank angle are presented in Table 4.…”
Section: Combustion Analysismentioning
confidence: 97%
“…Since the first patent of prechamber, developed by Ricardo [6], research has proven that this system is capable of operating with globally lean mixtures [7,8], rich in the prechamber and lean in the main chamber, increasing combustion speeds in lean conditions [9] and controlling the cyclic variations [10] through the high ignition energy provided by the prechamber [11,12]. Homogeneous or passive systems, where the air-fuel ratio is the same between auxiliary and main chamber, is simpler and less costly if compared to stratified or active systems, since they do not demand auxiliary systems for fuel supply.…”
Section: Introductionmentioning
confidence: 99%
“…As established by Peters [22], if chemistry is fast compared to transport processes, combustion takes place within asymptotically thin layers embedded in the flow. Applying this concept to jet ignition, the boundary of the jet may be seen as a continuous interface strained and convected by the flow [21] ( Fig. 12).…”
Section: Unsteady Flamelet For Ignition Prediction (Ufip) Modelmentioning
confidence: 99%
“…Sidey et al [21] proposed an original approach, similar to the Representative Interactive Flamelet (RIF) method of Peters et al [22,23,24], to study the ignition of a methane/air mixture by fully or partially burnt products: they used one-dimensional transient flamelets assuming that ignition occurs in thin layers between hot products and fresh mixture. It was shown that high scalar dissipation rates are able to freeze chemistry which is not fast enough to keep with mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2019) employed optical experiments (OH* chemiluminescence and Schlieren) in conjunction with 3-D Reynolds Averaged Navier Stokes (RANS) simulations to validate a new modelling approach for TJI based on the G-equation and investigate the combustion inside the main chamber. Studies on canonical configurations, such as the ones conducted in Sadanandan et al (2007), Fischer et al (2017a), Sidey and Mastorakos (2018), can yield further insights and enable to isolate the effect of mixing and chemical reactions on ignition initiation. A common observation is that ignition is unlikely to occur when mixing rate is very high or the hot jet temperature is low.…”
Section: Introductionmentioning
confidence: 99%